2021
DOI: 10.1002/hbm.25634
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use impacts pre‐stimulus neural activity in the visual cortices of people with HIV

Abstract: People with HIV (PWH) use cannabis at a higher rate than the general population, but the influence on neural activity is not well characterized. Cannabis use among PWH may have a beneficial effect, as neuroinflammation is known to be a critical problem in PWH and cannabis use has been associated with a reduction in proinflammatory markers. Thus, it is important to understand the net impact of cannabis use on brain and cognitive function in PWH. In this study, we collected magnetoencephalographic (MEG) brain im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 62 publications
(99 reference statements)
3
5
0
Order By: Relevance
“…compensate through increased oscillatory strength. These findings are consistent with previous literature that suggests both spontaneous and oscillatory power are altered in regular cannabis users (Edwards et al, 2009;Springer et al, 2021), and that cannabis use in PWH may have a neuroprotective effect, at least in some brain regions (Christopher-Hayes et al, 2021;Hall et al, 2021;Meade et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…compensate through increased oscillatory strength. These findings are consistent with previous literature that suggests both spontaneous and oscillatory power are altered in regular cannabis users (Edwards et al, 2009;Springer et al, 2021), and that cannabis use in PWH may have a neuroprotective effect, at least in some brain regions (Christopher-Hayes et al, 2021;Hall et al, 2021;Meade et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Finally, we also found that the association between the strength of spontaneous baseline activity and neural oscillations in the same spectral band was stronger in the dlPFC of cannabis users relative to nonusers, which may indicate that cannabis users are better able to compensate through increased oscillatory strength. These findings are consistent with previous literature that suggests both spontaneous and oscillatory power are altered in regular cannabis users (Edwards et al, 2009; Springer et al, 2021), and that cannabis use in PWH may have a neuroprotective effect, at least in some brain regions (Christopher-Hayes et al, 2021; Hall et al, 2021; Meade et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For somatosensory paradigms, epochs were of 0.3 s duration, with 0.0 s defined as stimulation onset and the baseline being the −0.05 to 0.0 s window. Epochs containing artifacts were excluded using a fixed threshold method (i.e., based on artifactual neural amplitude values), supplemented with visual inspection ( Christopher-Hayes et al, 2021 , Spooner et al, 2021a , Wiesman et al, 2021 ). Artifact-free epochs were time-domain averaged with respect to movement or stimulation onset.…”
Section: Methodsmentioning
confidence: 99%